2012
DOI: 10.1177/1721727x1201000208
|View full text |Cite
|
Sign up to set email alerts
|

Tooth Orthodontic Movement after Maxillofacial Surgery

Abstract: The purpose of this study is to compare the rate of orthodontic tooth movement in regenerated bone, created after mandibular Distraction Osteogenesis (DO), with the rate of orthodontic tooth movement in patients who had extractions. The sample group (treated subjects) was composed of 14 Class II patients (5 males and 9 females, mean age 25.0±1.1years) treated with a Distraction Osteogenesis appliance; the control group (extraction cases) was composed of 14 subjects (mean age 21.9±3.1 years). Both groups Were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…These technologies help create a better workflow for clinicians and have also helped in basic research such as with stem cells [50,51]. These technologies can also be used in other clinical aspects of dental research such as in orthodontics where a digital workflow can aid in accurately studying factors such as rate of tooth movement [52]. With advances in imaging technology and endodontic techniques, one can better assess the quality of fillings in the root canals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These technologies help create a better workflow for clinicians and have also helped in basic research such as with stem cells [50,51]. These technologies can also be used in other clinical aspects of dental research such as in orthodontics where a digital workflow can aid in accurately studying factors such as rate of tooth movement [52]. With advances in imaging technology and endodontic techniques, one can better assess the quality of fillings in the root canals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It appears that IL-36Ra and IL-38 had similar biological effects on LPS-induced IL-6 in human DCs, however, neither IL-36Ra nor IL-38 performs as a typical receptor antagonist, like IL-IRA (94)(95)(96)(97). Blocking the IL-36Ra or the IL-IR pathway mimicked the effects of IL-38 on the production of Th17 cytokines (98)(99)(100)(101)(102). It has been observed that IL-38 shares primary amino acid homology with ILIRa and IL-36Ra but is inconsistent with binding to the IL-18R (103)(104)(105)(106).…”
Section: Il-38 (Il-lflo)mentioning
confidence: 99%
“…This type of protocol should be used only in cases in which a more accurate radiographic evaluation is necessary, such as facial asymmetry, impacted teeth, orthognathic cases, etc. [ 30 , 31 ]. In these cases, in fact, CT images provide more accurate information than traditional X-ray techniques without a significant increase of radiological risk for the patients.…”
Section: Discussionmentioning
confidence: 99%